Determinan Perilaku Orang Membayar Pajak atau dan Zakat: - Panggiarti, Endang Kartini; Priyono, Nuwun; Iswanaji, Chaidir; Arifah, Siti; Alwi, Sofwan (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to analyze the determinants that influence individual behavior in paying taxes and or zakat, as well as examine the service quality of management institutions and the satisfaction of tax or zakat recipients. These factors are reliability, tangibles, empathy, responsiveness and adherence to stakeholder satisfaction. This research was conducted in the city and district of Magelang with a sample of 40 people. This research method uses a mix method, namely a quantitative approach (regression test), and a qualitative approach (case study). The results of the study show that only reliability has a significant positive effect on the level of satisfaction of zakat payers, while the other hypotheses have no positive and significant effect on both the satisfaction of zakat paying stakeholders and taxes. Keywords: Taxes, Zakat, Zakat Management Organizations, Amil Zakat Institutions